Effects of Regulated Deficit Irrigation on Yield and Yield Components of Capsoly Bean - Baghlani, Abdul Wahid; Saidi, Amirjan; Sarhadi, Wakil Ahmad; Haidari, Mohammad Daud (International Journal on Food, Agriculture and Natural Resources, 2025)
Common bean (Phaseolus vulgaris L.) is a key protein source but is limited by water stress. Water scarcity, worsened by climate change, particularly affects arid regions like Afghanistan. A two-year field experiment at Kabul University tested five irrigation treatments: full irrigation (CFI), deficit at vegetative (VD), flowering (FD), pod formation (PD), and grain-filling (GD) stages. Deficit irrigation during flowering and pod formation significantly reduced pod number, pod length, grains per pod, 100-grain weight, and yield, while deficits at vegetative and grain-filling stages had minimal effects. These findings indicate that common bean tolerates water stress during vegetative and grain-filling periods, but is sensitive during flowering and pod formation, highlighting the importance of irrigation timing for maximizing yield.